TiO2 nanoparticle coating for potential antimicrobial application in food industry - Othman, Siti Hajar; Abdul Rashid, Suraya; Mohd Ghazi, Tinia Idaty; Abdullah, Norhafizah (Faculty of Engineering, Universiti Putra Malaysia, 2012)
This work aims to develop titanium dioxide (TiO2) nanoparticle coating for potential antimicrobial application in food industry due to the unique and improved photocatalytic antimicrobial properties of the nanometer sized TiO2. TiO2 nanoparticles were produced by metal organic chemical vapour deposition (MOCVD) method and were dispersed and stabilized in aqueous suspension using polyacrylic acid (PAA). The suspension was then coated on quartz glass, whereby the light transmittance through the coated glass was determined using UV-vis spectrophotometer. The potential antimicrobial application of the nanoparticle coating was demonstrated via the agar diffusion test in which the coated glass was placed on the agar plate grown with the Escherichia coli (E. Coli) culture as the model microorganism. The concentration of E. Coli on the agar plate decreased upon illumination of UV light thus proved that the TiO2 nanoparticle coating exhibit antimicrobial activity.